Validation of The MPSIAC Model For Sediment Yield Prediction in Zargeh Watershed, Iran - Safamanesh, Ramin (2004)
Watershed degradation due to soil erosion and sedimentation is considered to be one of the major environmental problems in Iran. In order, to address the critical conditions of watershed degradation as well as insufficient availability of hydrometric stations, a study on the validity of an empirical model (Modified Pacific Southwest Inter Agency Model) developed in the arid and semi-arid conditions in United States to predict annual average sediment yield to Iranian watershed's condition was carried out. The MPSIAC model incorporates nine environmental factors that contribute to watershed's sediment yield. These factors are surface geology, soil, climate, runoff, topography, ground cover, land use, channel and upland erosion. In this study, the model was developed for Zargeh watershed with an area of 8.8 square kilometers. The sources data for the model was obtained from available records on rainfall and river discharge and sediment (collected over 20 years), topography, land use, geology and soil maps as well as from field surveys and laboratory analysis. Geographic Resources Analysis Support System (GRASS) GIs (version 5.0.0) was used to facilitate the spatial interpolation of the nine model parameters and interpretation of predicted sediment yield for the entire watershed. Twenty years sediment yield records fiom 1981 to 2000 were used to validate the simulated model results. Results of simple linear regression analysis between simulated results and actual field records indicated that there is a significant correlation (P < 0.05) with 2 = 0.6124 and standard error =2868.2 todyear. In the sensitivity analysis, it was found that the most sensitive parameters of the model in the order of importance are climate, channel erosion and runoff factors. Surfice geology, soil and slope factors were found to be insensitive to model output. The results of the study clearly indicated that the model can be applied to the Iranian conditions with recommended improvements be made on method to interpret upland erosion factor. The study also revealed that the model is more suitable for predicting yearly average sediment yield on a long time basis. The interest for this kind of model may be to establish for long term watershed management plans or for zoning of watershed's soil erosion potential where precise accuracy is not important.